Achieving partial denitrification using carbon sources in domestic wastewater with waste-activated sludge as inoculum. (July 2019) - Shi, Liangliang; Du, Rui; Peng, Yongzhen
Graphical abstract: Highlights: PD using carbon sources in domestic wastewater was achieved with pH, time control. NO2 − -N production reached 25.2 mg/L at an influent NO3 − -N of about 30 mg/L. PD performance remained effective without pH control after start-up. NO2 − -N production was related to consumed Ss with optimal Ss/NO3 − -N of about 3.5. Three genera were enriched and may be responsible for high NO2 − -N production. Abstract: Partial denitrification (PD, nitrate → nitrite) using carbon sources in domestic wastewater with waste-activated sludge as inoculum was firstly achieved in this study. Through controlling influent pH at about 9.0 and anoxic reaction time of 1 h in the start-up, the nitrite (NO2 − -N) production reached as high as 25.2 mg/L, with influent nitrate (NO3 − -N) of about 30 mg/L and chemical oxygen demand (COD) to NO3 − -N ratio of 5.9. Furthermore, PD performance remained stable without pH control during subsequent operations. Efficient NO2 − -N production was closely related to the consumed amount of readily biodegradable COD (Ss) fraction, with optimal Ss/NO3 − -N ratio of about 3.5. Thauera (19.1%), norank_f__Xanthomonadaceae (5.2%), and Thiobacillus (5.0%) were enriched during the 208-day operation, which may be responsible for high NO2 − -N production. These findings provided a novel strategy for promoting mainstream PD/Anammox application, without additional nitrite-accumulating denitrifying sludge and external carbon sources.